PREFERENSI RISIKO DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MASYARAKAT ILMIAH DALAM MENGONSUMSI PRODUK REKAYASA GENETIKA - Muhamad Agus Kurniawan; M. Rondhi (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2020)
The purpose of this study was to find out: the perception of Genetically Modified Organisms (GMO) Products and preferences of risk consuming GMO as well as the factors that influence decisions of the scientific community in consuming GMO. This research used descriptive and analytic method. Determination of the area by purposive method at the University of Jember. Method of determining the sample uses purposive sampling, namely students and lecturers from the Public Health Faculty and Agriculture Faculty. Furthermore, determining the number of samples using quota sampling, 150 students and 90 lecturers. The method of collecting survey data using questionnaires and data were analyzed based on questionnaires that returned and were responded to as many as 120 for students and 30 for lecturers. The results of the study show that (1) public perceptions regarding GMO based on health and agriculture are agreed, while the economy is hesitant. (2) risk of preference majority of the scientific community is a risk lover, which is as many as 80 people. (3) Factors that influence the scientific community's decision to consume GMO products significantly, type of work, age, amount of allowance or income per month, daily food expenditure, knowledge level and risk aversion level.